«The Secret History» – cultural heritage (Journal of Philosophy Culture and Political Science, 2018)
Article is devoted to the linguistic-philosophical analysis of a monument of writing of Mongol-Turkic culture of the 13-14th century of century. «The Secret History of the Mongols» when archetypes of modern culture and Mongols, and Kazakhs were formed. Special attention is paid to the text and an intertekst of «The Secret History of the Mongols» where codes of life of a nomad reveal through by means of genealogical interpretation. In this article the history of emergence, a way of distribution, degree of study of this subject on the basis of the analysis of concepts of the Japanese, Chinese, Russian and Mongolian researchers is considered. «The Secret History of the Mongols» acts as the invaluable monument of spiritual culture of medieval Turkic-Mongolian breeding associations testifying to their history, language, literature. The purpose of article is the comparative cultural-philosophical analysis of ethnographic sources and language of «The Secret History of the Mongols», history of writing and distribution of this monument of culture. In the course of the research the little-known oral sources which have found reflection in folklore of the people of Central Asia and Siberia have been revealed. Theoretical validity of article is based on the semiotics analysis of communicative systems of Mongolsand Turkic peoples in the context of cultures medieval Central Asian the nomadicheskikh of empires.Results of researches of the domestic and foreign scientists addressing the analysis of the text of «TheSecret History of the Mongols» act as a methodological basis. In work such methods, widespread inthe sphere of humanitarian and philosophical knowledge, as unity historical and logical, an ascensionmethod from abstract to concrete, from the general to the particular, a historical comparative, a hermeneuticsare widely applied. Bearing in mind that «The Secret History of the Mongols» it was earlier adequately investigatedby historians, linguists, literary critics, ethnographers, we have to consider this work with the culturalphilosophicalof positions now.Key words: «The Secret Tale», Genghis Khan, the Mongols, the Turks, the Tribe.